(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article, shows the strength, properties and production process of concrete, which is reinforced by dispersants. A composite is made by physically combining two or more materials (components) to produce a combination (blend) of structural properties not present in any individual component. They can, for example, provide greater strength and rigidity than is found in any of the separate components while being as light as possible